Abdominopelvic mass in postmenopausal female: a diagnostic dilemma - Pruthi, Neha; Suri, Jyotsna; Prasad, Saumya; Jain, Anil K.; Mittal, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Abdominopelvic masses have varied presentations and pose a diagnostic challenge especially in postmenopausal women where a detailed evaluation is needed to rule out malignancy. Here we report a case of postmenopausal woman with diagnostic discrepancies in clinical findings, radiological investigations and histopathological observation.